Cycle space : architecture & urban design in the age of the bicycle - Fleming, Steven (Rotterdam : nai010 publishers, 2012)
"From New York to Singapore, from Copenhagen to Sydney, from Chicago to Amsterdam, and from São Paolo to Budapest, there is a groundswell of cyclists taking to the streets of major cities. Whether death-defying bike messengers, hipsters with a taste for cycle chic, or commuters simply cycling to work, cycling is viewed as more than just an alternative. It's practical. It's cool. It's green. With portraits of major cities and their cycling cultures, this title is the first book to view the city through the lens of the bicycle, and offer a new ways of designing better cities. Cycle space is where architecture and urban design can begin to optimise conditions for cycling, and take inspiration from the aesthetics and ethics of cycling as well. It is where cities can begin reducing emissions, commute times, ill-health and sprawl."--Provided by publisher.
boek
Keywords: Urban transportation; Cycling; Bicycle lanes; City planning